1994
DOI: 10.1073/pnas.91.16.7668
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic resolution of in vivo phosphorylated and nonphosphorylated eukaryotic translation initiation factor eIF-4E: increased cap affinity of the phosphorylated form.

Abstract: Eukaryotic translation initiation factor eIF-4E plays a central role in the recognition of the 7-methylguanosine-containing cap structure of mRNA and the formation of initiation complexes during protein synthesis. eIF-4E exists in both phosphorylated and nonphosphorylated forms, and the primary site of phosphorylation has been identified. Previous studies have suggested that eIF-4E phosphorylation facilitates its participation in protein synthesis. However, the biochemical basis for the functional difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
198
8

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(220 citation statements)
references
References 43 publications
14
198
8
Order By: Relevance
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussioncontrasting
confidence: 50%
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussioncontrasting
confidence: 50%
“…Previously it was reported that p-eIF4E binds more efficiently to capped mRNAs (17), suggesting that the affinity of phosphorylated eIF4E for 4E-BP1 is decreased. Moreover, Chen et al (19) reported that p-eIF4E binds less well to 4E-BP1 than the unphosphorylated form.…”
Section: Discussionmentioning
confidence: 99%
“…Although eIF4E phosphorylation on Ser209 was discovered some time ago, it remains unclear whether phosphorylation increases or decreases eIF4E affinity for the cap-structure. Early data indicated that eIF4E phosphorylation increased the affinity for capped mRNAs, whereas other studies have shown that eIF4E phosphorylation actually decreases affinity for the cap-structure and capped oligoribonucleotides (15,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 98%
“…It has long been thought that phosphorylation increases the capbinding affinity of eIF4E. (49) Recent studies have now challenged this view (50,51) (discussed in Ref. 48).…”
Section: Introductionmentioning
confidence: 99%